2007
DOI: 10.1530/eje-06-0753
|View full text |Cite
|
Sign up to set email alerts
|

The sex-specific association of serum osteoprotegerin and receptor activator of nuclear factor κB legend with bone mineral density in older adults: the Rancho Bernardo Study

Abstract: Objective: The role of osteoprotegerin (OPG) and its receptor activator of nuclear factor kB legend (RANKL) in the regulation of bone in humans remain unclear. We examined the sex-specific associations of serum OPG, RANKL, and their ratio with bone mineral density (BMD) in older adults. Design: Participants were 681 community-dwelling adults, ages 45-90 years, who had serum OPG and RANKL measured and bone density scans in 1988-1991, with follow-up scans 5 and/or 10 years later. Methods: Analyses were sex-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 44 publications
4
51
1
1
Order By: Relevance
“…In our study, serum levels of OPG and RANKL were similar to previous reports [35,36] and comparable in both groups, although the groups were significantly different regarding BMD. In the literature, serum OPG and RANKL have been described to be associated with age and estradiol level, which were similar in both of our groups, with bone turnover, which was higher in our OP group, and with BMD status, which was lower in our OP group [35][36][37]. These last discrepancies may be explained by our limited sample size, but the strength of the correlation with BMD varies among studies.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, serum levels of OPG and RANKL were similar to previous reports [35,36] and comparable in both groups, although the groups were significantly different regarding BMD. In the literature, serum OPG and RANKL have been described to be associated with age and estradiol level, which were similar in both of our groups, with bone turnover, which was higher in our OP group, and with BMD status, which was lower in our OP group [35][36][37]. These last discrepancies may be explained by our limited sample size, but the strength of the correlation with BMD varies among studies.…”
Section: Discussionsupporting
confidence: 91%
“…In a study carried out by Anna Stern et al, to assess the level of OPG, RANKL and sexual steroids and associated with BMD found that with declining estrogen levels, RANKL is increased and thus BMD is reduced and the result is osteoporosis [33]. According to the results of the present study, OPG levels and bone mineral density were greater in the group receiving calcium, vitamin D and estrogen compared to the other groups.…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, high OPG levels were positively associated with BMD at the femoral neck in postmenopausal women in the Framingham offspring study [16]. Stern et al [17] also reported positive associations between OPG and BMD at the lumbar spine, total hip, and femoral neck among postmenopausal women who underwent estrogen therapy. However, a number of studies did not find significant associations between OPG values and BMD [18,19].…”
Section: Introductionmentioning
confidence: 94%